Targeted knockout of early nodulin-like 3 (MusaENODL3) gene in banana reveals its function in resistance to Xanthomonas wilt disease - Ntui, V.O.; Tripathi, J.; Shah, T.; Tripathi, L. (Wiley, 2024)
Nodulins and nodulin-like proteins play an essential role in the symbiotic associations between legumes and Rhizobium bacteria. Their role extends beyond the leguminous species, as numerous nodulin-like proteins, including early nodulin-like proteins (ENODL), have been identified in various non-leguminous plants, implying their involvement in functions beyond nodulation, such as nutrient transport and growth modulation. Some ENODL proteins have been associated with plant defense against pathogens, as evident in banana infected with Xanthomonas campestris pv. musacearum (Xcm) causing banana Xanthomonas wilt (BXW) disease. Nonetheless, the specific role of ENODL in plant defense remains to be fully elucidated. The MusaENODL3 gene was found to be repressed in BXW-resistant banana progenitor 'Musa balbisiana' and 20-fold upregulated in BXW-susceptible cultivar 'Gonja Manjaya' upon early infection with Xcm. To further unravel the role of the ENODL gene in disease resistance, the CRISPR/Cas9 system was employed to disrupt the MusaENODL3 gene in 'Gonja Manjaya' precisely. Analysis of the enodl3 edited events confirmed the accurate manipulation of the MusaENODL3 gene. Disease resistance and gene expression analysis demonstrated that editing the MusaENODL3 gene resulted in resistance to BXW disease, with 50% of the edited plants remaining asymptomatic. The identification and manipulation of the MusaENODL3 gene highlight its potential as a critical player in plant-pathogen interactions, offering new opportunities for enhancing disease resistance in crops like banana, an important staple food crop and source of income for resource-poor farmers in the tropics. This study provides the first evidence of the direct role of the ENODL3 gene in developing disease-resistant plants.